STUDY OF THE BEHAVIOUR PATTERN AND INDIVIDUALISATION OF FELIDAE FAMILY IN WILDLIFE FORENSICS - GURAV, TEJAL KRISHNA; ALCHI, AAEEN; CHAWLA, ARUSHI; PANDYA, SHIVANI R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Wildlife forensic is the implementation of the combined sciences, natural and cultural science. The court of law focused on the regulation of wildlife protection and conservation. Criminals that regulate illicit trade across nations and continents face the most significant threat. The tiger is the largest of all cats, the most iconic, and one of the most endangered. Due to its higher trading value, those animals are unlawfully slaughtered or poached for black-marketing, medical use and jewellery products. Tiger or leopard protection indirectly protects habitats and ecological health. By transmitting signals through vision, scent marks and voices, they are socially connected. Because of the dramatic reduction in tiger numbers, studying their behaviour habits is very difficult. Therefore, in this study, the Indian Leopard and Bengal Tigers [Felidae-family] are studied using the non-destructive approach through its claw nail markings. The transactional survey was the approach adopted for collecting data-signs of tiger nail bruises. This review focuses on the study of their behavioural habits and extensively study them for their conservation.